Cell viability assessment using the Alamar blue assay: A comparison of 2D and 3D cell culture models. Issue 1 (February 2015) - Bonnier, F.; Keating, M.E.; Wróbel, T.P.; Majzner, K.; Baranska, M.; Garcia-Munoz, A.; Blanco, A.; Byrne, H.J.
Highlights Protocols for cytotoxicological assessment of 3D cell cultures must be adapted. Collagen matrices induce a dilution of the effective cytotoxicity assay concentration. Diffusion and bioavailability of test substances in 3D matrices must be considered. Viability of immortalized cervical cells in 2D and 3D cell cultures are comparable. Results apply to cytotoxicity assays and to exposure protocols (nanoparticles/drugs).